Assessment of learners with dyslexic-type difficulties - Phillips, Sylvia (SAGE, 2018)
"This comprehensive guide enables teachers to understand a range of approaches to the assessment of children with dyslexic-type difficulties. It is an essential companion for those training to be specialist teachers of learners with dyslexia and a useful resource for all SENCOs, and teachers new or experienced."--Provided by publisher.